Between Educational Policies and Classroom Practices: A Quantitative Study on Translanguaging among Private School English Teachers in Tamil Nadu Context - Chris Alvin. A; John Love Joy. J (English Education Department at FKIP Nommensen University, 2026)
In Indian classrooms, the state of language pedagogy is becoming more aware of the role of translanguaging as a disruptive solution to the traditional language policing and monolingualism. Translanguaging enables the combination of the multilingual repertoires of students to reinforce the acquisition of the English language and also encourages cognitive development and independence among the learners. The present study is a quantitative research design, based on a structured questionnaire administered to 44 private school teachers in Tamil Nadu, India, to analyse the attitudes of teachers, their practices, and awareness about translanguaging in the classrooms. The results have shown that even the schools that only encourage monolingual English practices, most of the teachers often use their mother tongue, pictures, and emojis in their teaching in addition to English, which is a core practice of translanguaging. Despite the fact that the use of the mother tongue is still minimal, the teachers who use the mother tongue have reported positive experiences. This new, partial application of translanguaging is an effective agent of pedagogical transformation, and it provides a means to work against the strict language policies and create more inclusive learning conditions.